Pengaruh Budaya Organisasi Terhadap Kinerja Karyawan Rumah Sakit : Suatu Studi Systematic Literature Review (SLR) - Hasni Hanifah; Sri Wahyuni Sapri; Purwadhi Purwadhi; Yani Restiani Widjaja (BADAN PENERBIT STIEPARI PRESS, 2025)
This study aims to identify and systematically analyze the influence of organizational culture on employee performance in hospitals using the Systematic Literature Review (SLR) approach. Organizational culture is a set of values, norms, and beliefs that guide behavior within an organization, while employee performance reflects the effectiveness and productivity of individuals in carrying out their tasks. This study involved a critical review of 22 relevant national scientific articles published within the last five years (2020–2024). The synthesis results show that organizational culture significantly contributes to improving employee performance, both directly and through mediating variables such as work motivation, job satisfaction, and organizational commitment. Organizational culture is also proven to enhance the effectiveness of leadership, training, and management systems in creating a productive work environment. This study concludes that a strong, adaptive, and well-internalized organizational culture serves as a critical foundation for achieving optimal performance in the healthcare sector. The findings provide strategic implications for hospital management, human resource managers, and policymakers to prioritize organizational culture in institutional planning and development.